Consumers With Serious Mental Illness Perspectives on Care Integration: Preparation for Integration. (May 2022) - Fisher, Kathleen; Weissinger, Guy; O'Rorke, Rosemary; Edwards, Erica; Diamond, Guy
Background: Those with serious mental illness (SMI) experience poor health outcomes which may be addressed by the integration of mental health and primary care services. This integration could be enhanced by the inclusion of consumers in the planning process. Aims: This study sought to bring the voice of the consumer with SMI to assist with the integration of primary care and mental health services. Methods: Working with a community advisory board in the City of Philadelphia, we carried out a sequential explanatory mixed-methods study. The team conducted 12 focus groups ( n =149) and surveys ( n = 137) of consumers with SMI about their experiences of the health care system and perspectives on integrated health. Data from surveys and focus groups were analyzed and integrated. Results: Three relevant themes emerged: primary care experiences; health care stigma ; and social determinants as barriers to health. Generally, individuals with SMI supported the integration of care, with careful consideration given to social determinants of health, patient privacy, and respect between providers and patients. Conclusions: Integration may reduce health disparities experienced by individuals with SMI, but the process must be informed by intended consumers. Policymakers and administrators will need to address barriers to care, healthcare stigma, and social determinants of health. Nurses are well placed to inform and lead healthcare integration and overcome the siloing of mental and physical healthcare systems.